Soil microbial communities response to different fertilization regimes in young Catalpa bungei plantation - Guan, Zhuizhui; Lin, Daiyi; Chen, Dong; Guo, Yundan; Lu, Yizeng; Han, Qingjun; Li, Ningning; Su, Yan; Li, Jiyue; Wang, Junhui; Ma, Wenjun; Qiu, Quan; et al. (Frontiers in Microbiology, 2022)
Fertilization is a fundamental aspect of global forest management that enhances forest productivity and drastically affects soil microbial communities. However, few studies have investigated the differences and similarities in the responses of below-ground microbial communities to different fertilization schemes. The effects of fertilization regimes on the composition and diversity of soil fungal and bacterial communities were investigated in a young Catalpa bungei plantation in Shandong Province, Eastern China. Soil microbial communities were assessed undergoing three types of fertilization: (i) no fertilization (CK), (ii) hole fertilization (HF), and (iii) the integration of water and fertilizer (WF). We further analyzed the effects of soil depth (i.e., 0–20 and 20–40 cm) on the structure of soil microbial communities. Our results indicated that the diversity of bacteria (e.g., Chao1 and Shannon indices) reduced undergoing fertilization, and WF had a higher negative impact on bacterial diversity than HF. A lower bacterial diversity was observed in the subsoil compared to the topsoil. In contrast to bacterial diversity, fungal diversity had a slightly increasing trend in the fertilized environments. The primary bacterial function was metabolism, which was independent of fertilization or soil depth. Among fungal functional guilds, symbiotic soil fungi decreased obviously in the fertilized stand, whereas saprotrophic fungi increased slowly. According to the structural equation models (SEM), the diversity and composition of bacterial and fungal communities were jointly regulated by soil nutrients (including N and P contents) directly affected by fertilization and soil layer. These findings could be used to develop management practices in temperate forests and help sustain soil microbial diversity to maintain long-term ecosystem function and services.